OBJEKTIVITAS PEMBERITAAN VIRUS COVID-19 DALAM OKEZONE.COM - Benyamin Yosia (Jurnal Komunikasi dan Kajian Media, 2021)
This article discusses the media objectivity of okezone.com in reporting the covid-19 issue from December 31, 2019 to March 2, 2020. This research uses a quantitative content analysis method. To see the objectivity of the Covid-19 reporting, researchers used the theory of objectivity and risk communication, in order to see the objectivity of okezone.com information and the application of communication risk theory to reduce public health threats. The results of this study indicate that okezone.com is not yet objective because it does not provide continued hyperlinks and only uses one side of coverage..